Land Utilization, Perspectives, Implementation and the Problems in the Development of Sustain Able Tourism in the Global Era - I Gede Arya Bagus Wiranata (Sociological Jurisprudence Journal, 2022)
Sustainable Tourism often watches videos and is echoed by tourism experts around the world. The aims of this research are to discuss the use of Land, Investment, Tourism, Local Wisdom and Globalization and to find out the problem of the availability of land in Bali. This study uses a normative research method by combining land and tourism regulations. The result of this research shows that Tourism activities require the conversion of land, land and resources. In the context of globalization, the presence of investors from one country to another is a necessity. The current problems related to land are exacerbated by the emergence of: (a) Globalization, (b) Socio-cultural changes, (c) orientation of shifting values towards materialistic (d) Changes in patterns and lifestyles increasingly towards consumerism, (e) Individualistic and hegemony personal.